Comparison of circulation parameters and some motoric adaptations of futsal athletes and sedentaries (Revista de Investigaciones Universidad del Quindío, 2022)
The aim of this study is to compare the circulation parameters and some motoric adaptations of futsal athletes aged 15-17 and sedentary individuals. For this purpose, an athlete and a sedentary group was formed and a total of 30 volunteers were included in the study. Individuals were included among futsal athletes and individuals who participated in futsal auditions. Saturation, heart rate and blood pressure values were recorded in order to examine the circulation parameters from all individuals. As a result, a high rate of change was not observed in the circulation values of sedentary and futsal athletes. As a result of regular training, an increase in performance was observed on motoric characteristics. It can be concluded that individuals can improve their motoric features and increase their performance by doing sports.
Keywords: Training; Futsal; adaptation; sedentary